Co-creation in Macrotask Knowledge Work on Online Labor Platforms - Seppänen Laura; Spinuzzi Clay; Poutanen Seppo; Alasoini Tuomo (VIA University College, 2025)
Nordic working life studies have mostly focused on the precarious aspects of work mediated via online labor platforms. We follow a different approach and examine the potential of such work to benefit professionals by enhancing their job quality and learning. This qualitative, practice-based study applies the concept ‘co-creation’ to examine how a social form of creating value takes place in Upwork macrotask projects. It then investigates how platform features shape opportunities for co-creation. The data comprise interviews of 15 freelancers residing in Finland. The findings sug-gest that co-creation is possible in macrotask projects, but the platform does not seem to actively support co-creation. This paper provides insights into the discussion of job quality at platform work and how co-creation on platforms might be developed to support the Nordic labor market model.